Simplified analytical models for hypersonic lateral-directional stability. (September 2022) - Guo, Shuai-Qi; Liu, Wen; Zhang, Chen-An; Zhou, Xiang; Wang, Fa-Min
Abstract: The balance of lateral and directional static stability plays an important role in the lateral-directional dynamics and vehicle design. The theory of geometric influence on the lateral and directional static stability is mature for conventional aircrafts. However, the distinct configuration characteristics and flow physics for hypersonic vehicles may lead to different design theory, which is absent now. In order to solve this problem, simplified analytical models of lateral-directional static derivatives are proposed based on the simplified geometry model. It's found that the lateral and directional stability both increase as the deflection angle, dihedral angle, or angle of attack increases, whereas the influence of sweep angle can be neglected. The difference lies in that the lateral stability is proportional to dihedral angle while the directional stability is proportional to the square of dihedral angle. The reasonable accuracy is validated in comparison with the inviscid numerical solutions. Furthermore, the influence mechanism of viscous effects on the lateral and directional stability is investigated in detail based on the numerical results. It's found that the strong viscous interaction can improve the lateral stability evidently, and both the strong viscous interaction and the shear stress can lead to the increase of the directional stability. In addition, the lateral stability is slightly reduced by the chemical nonequilibrium effects. Highlights: The proposed analytical models can clearly reveal the relationship between the main geometric features and the hypersonic lateral-directional stability. The lateral stability is proportional to dihedral angle. The directional stability is proportional to the square of dihedral angle. The lateral stability can be improved by the strong viscous interaction effects. The directional stability can be improved by both the strong viscous interaction effects and the shear stress.